Some English-Medium Primary School Teachers’ Perspectives of Using a Drama-Based Approach to Teach Irish - Barry, Jennifer (Marino Institute of Education, 2018)
This dissertation examines a number of English-medium primary school teachers’ perceptions of using a drama-based approach to teach Irish. A tool of communicative language teaching (CLT), drama is often employed as a methodology in additional language teaching, particularly English as an additional or second language (EAL/ESL). However, little research has been undertaken in relation to whether drama is used to teach the Irish language. What does exist contains little reference to teachers’ own attitudes or experiences. A semi-structured interview approach was taken in gathering the data. After analysing six interviews carried out with primary teachers aged 23-33, this dissertation establishes that whilst all teachers interviewed find a drama-based approach to be beneficial in the acquisition of Irish, it remains a peripheral methodology for most teachers. This is due to teachers’ self-acknowledged own lack of confidence in using the Irish language. The dissertation examines the four themes that emerged through analysis of the data: drama as incentivised learning, drama as a tool for learning, transforming Irish from a subject to a language through drama, and teachers’ underlying relationship with Irish. The findings of this dissertations suggest that further research could be undertaken in this area to establish a broader breadth of coverage. In doing so, the valuable view points and experiences of teachers would be highlighted, providing a deeper insight into the relationship between the Irish language and the education system.
Keywords: Research Subject Categories::SOCIAL SCIENCES; English Medium; Irish primary schools; Communicative language teaching (CLT); English as a second language (ESL); Drama; Irish language